Knowledge, practice and emotional status related to COVID-19 pandemic among radiology technicians working at pandemic hospitals - AKYURT, NURAN (ELSEVIER IRELAND LTD, 2021)
Purpose: This study aimed to evaluate knowledge, attitude, practice and emotional and psychological concerns related to COVID-19 pandemic among radiology technicians working at pandemic hospitals across Turkey Methods: A total of 228 radiology technicians working at pandemic hospitals across Turkey were included on a voluntary basis in this questionnaire-based online survey The questionnaire form elicited items on socio-demographic and occupational characteristics and personal opinions and experience on COVID-19 outbreak and related protective strategies, along with survey scales including Knowledge on COVID-19 Outbreak Scale (KCS), Knowledge on Protective Strategies for COVID-19 Scale (KPSCS), General Preventive Practices for COVID-19 Scale (GPPCS), Emotional State Scale (ESS) and Fear of COVID-19 Scale (FCS). Results: Males had lower ESS (p = 0.004) scores and higher FCS (p = 0.026) scores than females. Having a COVID-19 training (63.4 %) was associated with higher KCS (p = 0.006) and PSCS (p < 0.001) scores, while higher KCS was also related with higher PSCS (p < 0.001) and GPPCS (p < 0.0001) and lower ESS (p = 0.004) scores. Those who had knowledge on the facility safety (56.6 %) and risk management (59.2 %) plans had higher scores on KCS, PSCS, GPPCS and FCS, while had lower scores on ESS (p < 0.05 for each). Conclusions: Our findings revealed association of female gender, co-morbid psychiatric disease, lack of training unawareness of safety and risk management plans, lack of experience in COVID-19 imaging and high workload with higher risk of poor emotional state and/or intense fear of the disease among radiology technicians during pandemic.
Keywords: COVID-19 pandemic; Radiology technicians; Knowledge; Attitude; Practice; Emotional state; HEALTH-CARE WORKERS; PSYCHOLOGICAL IMPACT; RADIATION SAFETY; OUTBREAK; AWARENESS; ANXIETY